The receipt of the human papillomavirus vaccine’s influence on future human papillomavirus vaccine recommendations by medical and dental studentsWhy Is This Important? - Ana Karina Mascarenhas, BDS, MPH, DrPH; Arati Kelekar, MD; Victoria C. Lucia, PhD; Nelia M. Afonso, MD (JADA Foundational Science)
Background: With a growing vaccine-hesitant population and with the increase in oral cancers, particularly in a younger population, there is a heightened need for dental and medical providers to advocate for vaccination, including the human papillomavirus (HPV) vaccine. This study aimed to assess HPV vaccine knowledge, personal immunization status, and attitudes and opinions of dental students (DSs) and medical students (MSs). Methods: Students from 1 medical and 4 dental schools in the United States completed an anonymous online survey assessing knowledge and attitudes and opinions about the HPV vaccine, including personal HPV vaccine status and confidence in vaccine counseling. Results: Seventy percent of the 453 students who completed the survey were vaccinated for HPV. Male students were significantly less likely to have received the HPV vaccine (odds ratio [OR], 0.37; 95% CI, 0.24 to 0.56). MSs were 1.75 times more likely to have received the HPV vaccine than DSs (95% CI, 1.16 to 2.63). Those who were vaccinated and those who were not vaccinated substantially differed in opinions and knowledge of the HPV vaccine. Vaccinated students were more than 5 times more likely to report they would recommend HPV vaccines to friends and family (OR, 5.22; 95% CI, 2.57 to 10.87), recommend HPV vaccines to patients (OR, 2.71; 95% CI, 1.39 to 5.26), and advocate for HPV vaccines (OR, 2.42; 95% CI, 1.24 to 4.70). In the linear regression model, age (P = .0204 and P < .00003), profession (P < .00001), and HPV vaccination status (P < .00001) predicted HPV knowledge. Conclusions: These findings show that MSs are more likely to be vaccinated. In addition, HPV-vaccinated people had better knowledge, attitudes, and opinions than those who were not vaccinated. Receipt of the HPV vaccine increased advocacy for the vaccine. Educating these professionals about the efficacy and impact of the HPV vaccine could increase their advocacy for the vaccine.